Articulating the Interests of Disability Groups: Utilization of Social Media in Kudus Regency, Indonesia - Zaini, Ahmad; Qodarsasi, Umi; Fawwaz, Muhammad (KOMUNIKA: Jurnal Dakwah dan Komunikasi, 2024)
As a minority group, Disability Communication Forum of Kudus Regency (FKDK) uses social media to advocate and carry out social change. This research aims to explore the utilization of social media to articulate the interests of disability groups. This research employed a descriptive-qualitative method. The primary data are collected from in-depth interviews with the chairman of a disability organization, disability activists, and a regional parliament member. Meanwhile, the secondary data are collected from journals, books, and websites related to this issue. This research defines social media usage for Disability Communication Forum of Kudus Regency (FKDK) to encourage the passing of Local Regulations regarding the protection and fulfillment of disability rights. They mobilize communities, raise awareness through sharing videos and photographs, and use media as a fundraising instrument. Social media empowers marginalized groups by providing a platform to articulate their interests, advocate for rights, and facilitate social justice movements. It enhances accessibility, promotes community mobilization, and offers innovative fundraising opportunities. Advocacy groups leverage social media strategically for policy influence, public engagement, and collaboration. However, addressing digital regulation is crucial to ensure inclusivity and digital advocacy endeavors benefit all community members.